Potential cryptic speciation in Mediterranean populations of Ophioderma (Echinodermata: Ophiuroidea) - Stöhr, Sabine; Boissin, Emilie; Chenuil, Anne (Zootaxa, 2009)
Ophioderma longicauda is a large brittlestar species, common in the Mediterranean Sea and spread across the subtropical-tropical eastern Atlantic Ocean. Recently, a morphologically similar brooding form of O. longicauda was discovered in the eastern Mediterranean Sea. The brooding period is restricted to late May and early June and the largest females brood over 1,000 juveniles, all of the same ontogenetic stage. Brooders differ from non-brooding O. longicauda in body colour (dominated by green instead of red), gonad colour (in alcohol white instead of oliveto reddish-brown) and size (up to 17 mm disk diameter instead of 30 mm). These characters overlap between both forms though. Molecular data (mt-COI sequences) lend weak support to the existence of two separate species, but suggest that if a split occurred it is recent and both forms interbreed. Alternatively, the eastern Mediterranean populations could represent a poecilogonous subgroup of O. longicauda.